ANALYSING THE TEACHER'S APPLICATION OF LINGUISTICS COMPETENCE IN ENGLISH LEARNING AND TEACHING - Rabbani, Bariq Hammam; Sumarni, Sri; Dewanti, Ratna (Universitas PGRI Sumatera Barat, 2023)
In order to promote students' language development, teachers in lower and higher education must have a working grasp of English linguistics. This article used a video from the YouTube platform to analyze the teacher's Application of linguistics in an English learning and teaching situation. The researcher employed content analysis of qualitative research in this study. In order to explore how analysing the teacher’s understanding of linguistics in an English learning and teaching through YouTube platform, this study answers the following research question, by analysing the recorded video sessions from a YouTube, what linguistic aspect is used by the English teacher in the teaching Biography and Analytical Exposition? And how does the teacher used linguistic knowledge of the mostly found in linguistic aspect? One senior high school teacher was paired with 22 students in this YouTube video. The teacher was enrolled in 11 class at Senior high school that focused on Biography and Analytical Exposition. The goal of this study is to determine teacher understanding in order to investigate the benefits of this reflective activity on their linguistics knowledge.